Accelerating effect of catalase on microbiologically influenced corrosion of 304 stainless steel by the halophilic archaeon Natronorubrum tibetense. (January 2021) - Qian, Hongchang; Zhang, Dawei; Cui, Tianyu; Chang, Weiwei; Cao, Fahe; Du, Cuiwei; Li, Xiaogang
Highlights: Variation of catalase concentration in the inoculated medium was characterized. Catalase promoted the pitting corrosion of stainless steel in the inoculated medium. SECM was used to study the effect of catalase on MIC. COMSOL simulation was applied to explain the change of SECM current density. Catalase mainly accelerated the cathodic oxygen reduction process of MIC. Abstract: The role of metabolic catalase in microbiologically influenced corrosion (MIC) of 304 stainless steel by Natronorubrum tibetense was investigated. Under sterile condition, the catalase concentration in the culture medium had no effect on the corrosion of stainless steel. In contrast, the addition of catalase in the inoculated culture medium resulted in more severe pitting corrosion of stainless steel. The potentiodynamic polarization results demonstrated that catalase mainly promoted the cathodic process of MIC of the stainless steel. Scanning electrochemical microscopy (SECM) further confirmed the accelerating effect of catalase on the cathodic oxygen reduction reaction of MIC.